Synchronized Sharia Reorganization of Coastal MSMEs: A Structural Model of Digital Transformation, Green Economy, Islamic Capital, and Multi-Stakeholder Collaboration - Dewi Sundari Tanjung; Azhari Akmal Tarigan; Zuhrinal M. Nawawi (Women, Education, and Social Welfare, 2026)
This study tests a livelihood-oriented model of micro, small, and medium enterprise (MSME) reorganization in Sibolga City, Indonesia. Using survey data from 150 coastal food MSME actors and partial least squares structural equation modeling, the study examines whether Sharia digital transformation, Sharia green economy orientation, and Islamic capital enhance MSME reorganization directly and indirectly through multi-stakeholder collaboration. All direct paths are positive and significant (p < .001). Collaboration is the strongest predictor of reorganization (β = .556) and partially mediates the effects of digital transformation, green orientation, and Islamic capital. The model explains 41.7% of collaboration and 71.2% of reorganization. Multi-group analysis shows that digital transformation is more influential among enterprises with higher platform readiness, whereas green orientation, Islamic capital, and collaboration remain stable across groups. The study introduces a Synchronized Sharia Reorganization Model that treats technology, ecological responsibility, ethical-relational resources, and institutional coordination as complementary capabilities. The findings support inclusive coastal livelihood policy, particularly for women-participatory, household-based food enterprises.